1975
DOI: 10.1287/trsc.9.3.248
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioural Explanation of the Association Between Bus and Passenger Arrivals at a Bus Stop

Abstract: The times of arrivals of passengers and departures of buses have been observed at ten bus stops in suburban London. The different bus stops were observed at different times of the day, but the observations at each were repeated at the same time on each of eight different days. Due to the predictability of the bus services, passengers' waiting times were observed to be about 30 per cent less than they would have been had the passengers arrived at random times. An explanation of this involves considering passeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 0 publications
4
40
0
1
Order By: Relevance
“…Okrent (1974) found that a headway of 12 to 13 minutes marks a transition period, where a much greater fraction of people is aware of the schedule. Similar results were obtained by Jolliffe and Hutchinson (1975) and Marguier and Ceder (1984). Coslet (1976) used utility theory to predict the arrival time of aware passengers.…”
supporting
confidence: 90%
“…Okrent (1974) found that a headway of 12 to 13 minutes marks a transition period, where a much greater fraction of people is aware of the schedule. Similar results were obtained by Jolliffe and Hutchinson (1975) and Marguier and Ceder (1984). Coslet (1976) used utility theory to predict the arrival time of aware passengers.…”
supporting
confidence: 90%
“…Travel times of the buses between each pair of stops are distributed as Lognormal with a mean of 0.77 min and variance of 0.4 [13,24]. At each stop, passengers arrive randomly using a Poisson distribution with rate equal to one [16]. The mean of the distributions are the parameters used by our model.…”
Section: Resultsmentioning
confidence: 99%
“…When evaluating an SP, it is important to differentiate low-frequency services and high-frequency services (Turnquist, 1982): in low frequency services, passengers arrive at the bus stops shortly before the bus's scheduled services, whereas in high-frequency services, the customers tend to arrive at the stops randomly ( Jolliffe & Hutchinson, 1975;Turnquist, 1978;Bowman & Turnquist, 1981;Ceder & Marguier, 1985). In the first scenario, punctuality is the main metric, whereas the service regularity is the most important metric in high-frequency routes.…”
Section: Evaluation Metricsmentioning
confidence: 99%